1993
DOI: 10.1055/s-2008-1063542
|View full text |Cite
|
Sign up to set email alerts
|

Recent Evaluation of Prognostic Risk Factors in Esophageal Atresia - A Multicenter Review of 223 Cases

Abstract: In this study, 223 cases of esophageal atresia (Type IIIb: 85.7%; Type II: 5.8%; Type IIIc: 4.0%; Type IIIa: 2.2%; Type IV: 2.2%) from 6 pediatric surgery centers of Austria, were retrospectively examined for the following parameters and their influence on the prognosis: Birth weight (2494.7 +/- 702.0 g), gestation week (range 27-42 weeks; mean 37.3 +/- 3.1 weeks), sex (male: n = 128; female: n = 95), long-gap atresia (> or = 2 cm: n = 33), Tracheomalacia (n = 16), associated malformations (n = 122; cardiac 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 8 publications
1
6
0
2
Order By: Relevance
“…The incidence of chromosomal abnormalities and VACTERL association remained similar and unchanged over time in our study as reported by Tönz et al [4], but in contrast to our findings they did not show any increase in the presence of major cardiac anomalies. Other patient characteristics such as sex ratio, birth weight, gestational age and type of atresia are comparable with other reports [4,5,[13][14][15]. Several risk factors have previously been identified for the outcome in patients with EA.…”
Section: Discussionsupporting
confidence: 80%
“…The incidence of chromosomal abnormalities and VACTERL association remained similar and unchanged over time in our study as reported by Tönz et al [4], but in contrast to our findings they did not show any increase in the presence of major cardiac anomalies. Other patient characteristics such as sex ratio, birth weight, gestational age and type of atresia are comparable with other reports [4,5,[13][14][15]. Several risk factors have previously been identified for the outcome in patients with EA.…”
Section: Discussionsupporting
confidence: 80%
“…Remarkably, only one randomized control trial 18 and seven prospective studies 3,12-17 could be included in this study. A limited number of multicenter studies 1,3,12,13,21,39,[45][46][47][48] reported on their experiences, whereas the majority presented single center data. Likewise, also comparative studies were rare.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the mortality rate is double in cases which have associated anomalies. [3,6] Iuchtman M et al, also showed 24% more mortality rate in cases with associated anomalies, than without any anomalies. [18] In our study group, survival rate was 88.9%, 90%, 75% and 18%, respectively, for no associated anomalies, single associated anomaly, two associated anomalies and >2 associated anomalies, with an overall survival of 79.7%.…”
Section: Discussionmentioning
confidence: 95%